Trends in Meningococcal Disease in the United States Military, 1971–2010 - Michael P. Broderick; Dennis J. Faix; Christian J. Hansen; Patrick J. Blair (Emerging Infectious Diseases, 2012)
Meningococci have historically caused extensive illness among members of the United States military. Three successive meningococcal vaccine types were used from 1971 through 2010; overall disease incidence dropped by >90% during this period. During 2006–2010, disease incidence of 0.38 (cases per 100,000 person-years) among members of the US military was not significantly different from the incidence of 0.26 among the age-matched US general population. Of the 26 cases in the US military, 5 were fatal, 15 were vaccine failures (e.g., illness in a person who had been vaccinated), and 9 were caused by Neisseria meningitidis serogroup Y. Incidences among 17- to 19-year-old basic trainees and among US Marines were significantly higher than among comparison military populations (p<0.05). No apparent change in epidemiology of meningococcal disease was observed after replacement of quadrivalent polysaccharide vaccine with conjugate vaccine in 2007. The data demonstrate that vaccination with meningococcal vaccine is effective.